Draft genome sequencing and annotation of a low-virulence Morganella morganii strain CQ-M7, a multidrug-resistant isolate from the giant salamander in China. (March 2020) - Zhao, Guangwei; Luo, Zeli; Wang, Yan; Liu, Jia; Wu, Di; Zhang, Liwu; Yang, Xiaowei
Highlights: A multidrug-resistant Morganella morganii strain was isolated from the Chinese giant salamander in China. Draft genome sequence and annotations were deposited in GenBank under accession number RQIJ00000000 . Five antimicrobial resistance genes – aadA1, rmtB, bla CIT, bla CMY-1 and bla DHA – were harboured in the isolate. Abstract: Objectives: A multidrug-resistant Morganella morganii strain (CQ-M7), isolated from the kidney of a diseased Chinese giant salamander in China, was examined with whole genome sequencing to better understand drug tolerance and its pathogenicity. Methods: The draft genome of the investigated strain was assembled using HGA assembler and annotated using Rapid Annotations Subsystems Technology (RAST) server. The contigs were annotated by the appropriate bioinformatics tools available on the National Center for Biotechnology Information (NCBI) website. Antibiotic resistance genes were detected by PCR. Pathogenicity of the isolate was performed on 30 healthy Chinese giant salamanders with different infection dosages. Results: The CQ-M7 strain showed resistance to multiple antimicrobials, especially to aminoglycoside and β-lactam antibiotics. Seventeen drug-resistance genes were detected, which were related to β-lactams, aminoglycosides, fluoroquinolones, tetracyclines, peptide antibiotic, and fosfomycin resistance. Sequence analysis showed the assembled genome size to be 4 966 326 bp with 51.16% of GC content, containing 4587 protein-coding genes, 71 pseudogenes, five rRNAs, 80 tRNAs, and five noncoding RNAs. The genome sequence was deposited in GenBank under accession number RQIJ00000000 . Artificial infection results indicated that the CQ-M7 strain was a low-virulence strain for the Chinese giant salamander. Conclusion: It is believed that this is the first draft genome of Chinese giant salamander original Morganella morganii strain harbouring multiple antibiotic resistance genes in China. The reported genome sequence could provide insights into antibiotic resistance mechanisms and control strategies of Morganella morganii .